Reasons for Seeking HIV-test: Evidence from a Private Hospital in Rural Andhra Pradesh, India - Sivaram, Sudha; Saluja, Gurcharan Singh; Das, Manik; Reddy, P Sudhakar; Yeldandi, Vijay (Journal of Health, Population and Nutrition, 2009)
This study sought to describe the development of HIV counselling and testing services in a rural private hospital and to explore the factors associated with reasons for seeking HIV testing and sexual behaviours among adults seeking testing in the rural hospital. Data for this study were drawn from a voluntary counselling and testing clinic in a private hospital in rural Andhra Pradesh state in southern India. In total, 5,601 rural residents sought HIV counselling and testing and took part in a behavioural risk-assessment survey during October 2003-June 2005. The prevalence of HIV was 1.1%. Among the two reported reasons for test-seeking - based on past sexual behaviour and based on being sick at the time of testing - men, individuals reporting risk behaviours, such as those having multiple pre- and postmarital sexual partners, individuals whose recent partner was a sex worker, and those who reported using alcohol before sex, were more likely to seek testing based on their past sexual behaviour. Men also were more likely to seek testing because they were sick. The findings from this large sample in rural India suggest that providing HIV-prevention and care services as part of an ongoing system of healthcare-delivery may benefit rural residents who otherwise may not have access to these services. The implications of involving the private sector in HIV-related service-delivery and in conducting research in rural areas are discussed. It is argued that services that are gaining prominence in urban areas, such as addressing male heterosexual behaviours and assessing the role of alcohol-use, are equally relevant areas of intervention in rural India. Key words: HIV; HIV infections; Acquired immunodeficiency syndrome; Private sector; Rural health serÂvices; Voluntary counselling and testing; India doi:10.3329/jhpn.v26i4.1885 J Health Popul Nutr 2008 Dec:26(4):431-441